FIQH JINAYAH IN THE DIGITAL ERA: ANSWERING THE CHALLENGES OF DEEPFAKE PORNOGRAPHY FROM THE PERSPECTIVE OF MAQĀṢID AL-SYARĪ‘AH - M. Yushlih Dg. Sitonra; Alfiansyah Anwar; Saidah Saidah; Azlan Thamrin (QANUN: Journal of Islamic Laws and Studies, 2026)
The development of Artificial Intelligence (AI) technology has given rise to the deepfake phenomenon, an audio-visual manipulation that mimics a person's face and voice with a high degree of similarity. The misuse of deepfakes in the creation of pornographic content raises serious issues related to privacy violations, the destruction of dignity, and the lack of legal norms. National regulations such as the Electronic Information and Transactions Law (UU ITE) and the Pornography Law do not specifically address AI-based digital crimes, so an Islamic legal perspective is needed to provide a more comprehensive normative approach. This study aims to analyze the phenomenon of deepfake pornography through the framework of Islamic jurisprudence (fiqh jinayah) by emphasizing the principle of maqāṣid al-syarī‘ah, particularly the protection of honor (ḥifẓ al-‘ird). The research method used is qualitative with a normative-juridical approach through a literature study of Islamic legal sources and contemporary legal studies. The results of this study indicate that Islamic jurisprudence (fiqh jinayah) has high flexibility in responding to new crimes unknown in classical literature through the concept of ta'zīr and the principle of benefit (maṣlaḥah mursalah). The maqāṣid al-syarī‘ah approach strengthens the ethical basis to emphasize that the distribution of deepfake pornography content is a violation of human dignity and must be sanctioned based on the principles of substantive Islamic justice. Thus, Islamic jurisprudence (fiqh jinayah) and maqāṣid al-syarī‘ah can be an alternative paradigm in formulating contemporary Islamic legal policies to protect human dignity in the digital era.